Strategi Penggalangan Dana Masjid Berbasis Online Melalui Website Dan Crowdfunding - Haidar, Muhammad Hilmy; Primadewi, Ardhin; Nugroho, Setiya (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
There are problems in managing mosque fundraising, namely lack of clarity and lack of responsibility in reporting which can cause mosque financial reports to the congregation to be simplistic.This research examines various aspects that need to be considered when raising funds for mosques via online platforms or involving websites and crowdfunding. The focus of the research is focused on analyzing strategies, obstacles and solutions that arise in implementing mosque fundraising using website and crowdfunding platforms. The aim of this research is to analyze the system creation process that emerges in implementing mosque fundraising using website and crowdfunding platforms. The method used in this research is a software development method which involves steps such as communication, planning, system design, program creation, and system testing. The system can operate effectively and meet user needs as well as the mosque's fundraising goals. Evaluation of feedback from users during testing helps determine the extent to which the system meets their expectations and needs.